Inflammasome activation by viral infection: mechanisms of activation and regulation - Shi, Wen; Jin, Mengyun; Chen, Hao; Wu, Zongxue; Yuan, Liuyang; Liang, Si; Wang, Xiaohan; Memon, Fareed Uddin; Eldemery, Fatma; Si, Hongbin; Ou, Changbo (Frontiers in Microbiology, 2023)
Viral diseases are the most common problems threatening human health, livestock, and poultry industries worldwide. Viral infection is a complex and competitive dynamic biological process between a virus and a host/target cell. During viral infection, inflammasomes play important roles in the host and confer defense mechanisms against the virus. Inflammasomes are polymeric protein complexes and are considered important components of the innate immune system. These immune factors recognize the signals of cell damage or pathogenic microbial infection after activation by the canonical pathway or non-canonical pathway and transmit signals to the immune system to initiate the inflammatory responses. However, some viruses inhibit the activation of the inflammasomes in order to replicate and proliferate in the host. In recent years, the role of inflammasome activation and/or inhibition during viral infection has been increasingly recognized. Therefore, in this review, we describe the biological properties of the inflammasome associated with viral infection, discuss the potential mechanisms that activate and/or inhibit NLRP1, NLRP3, and AIM2 inflammasomes by different viruses, and summarize the reciprocal regulatory effects of viral infection on the NLRP3 inflammasome in order to explore the relationship between viral infection and inflammasomes. This review will pave the way for future studies on the activation mechanisms of inflammasomes and provide novel insights for the development of antiviral therapies.